2016
DOI: 10.1002/etc.3476
|View full text |Cite
|
Sign up to set email alerts
|

Combining exposure and effect modeling into an integrated probabilistic environmental risk assessment for nanoparticles

Abstract: There is a growing need for good environmental risk assessment of engineered nanoparticles (ENPs). Environmental risk assessment of ENPs has been hampered by lack of data and knowledge about ENPs, their environmental fate, and their toxicity. This leads to uncertainty in the risk assessment. To deal with uncertainty in the risk assessment effectively, probabilistic methods are advantageous. In the present study, the authors developed a method to model both the variability and the uncertainty in environmental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The multimedia model SB4N can also accommodate various spatial scales, like regional, continental, and global, but always calculates one average concentration for soil, sediment, air, lake, river, and seawater. It is possible, however, to run models like SB4N for a certain grid, within an overarching model that provides input on a scale of, for instance, 200 Â 200 km [118].…”
Section: Comparing the Models: What Model For Whichmentioning
confidence: 99%
See 1 more Smart Citation
“…The multimedia model SB4N can also accommodate various spatial scales, like regional, continental, and global, but always calculates one average concentration for soil, sediment, air, lake, river, and seawater. It is possible, however, to run models like SB4N for a certain grid, within an overarching model that provides input on a scale of, for instance, 200 Â 200 km [118].…”
Section: Comparing the Models: What Model For Whichmentioning
confidence: 99%
“…Exposure then can be combined with effect thresholds in a PEC/NEC (NEC is the no-effect concentration) approach, where the NEC may come from data for different dose response models dependent on the AOP (threshold model, log logistic, Weibull, binary). Due to considerable uncertainty compared to ERA for traditional chemicals, probabilistic approaches are recommended, which can be adopted from recent developments in the ERA of engineered nanoparticles [118].…”
Section: Fate and Exposure Models In The Context Of Era For Plastic Imentioning
confidence: 99%
“…However, the extensive utilization of ENPs has resulted in their inevitable and irreversible release into the environment [4]. With ENPs expected to become more widely used, their effect on the environment and organisms has been an increasing cause of concern [5][6][7][8]. As plants interact with the atmosphere, soil, and water, they might be directly contaminated by ENPs.…”
Section: Introductionmentioning
confidence: 99%
“…The approach has been used for single substances (van der Voet and Slob, 2007;Bokkers et al, 2009;Jacobs et al, 2015) and for mixtures, using a dose-addition model , Müller et al, 2009. The approach has also been used in the ecological area (Jacobs et al 2016 (OECD, 2018). ECPA "Line 1748ff: It should be added that the data by Price et al I for surface water samples have shown that in the vast majority of cases, environmental risk is dominated by one or very few chemicals.…”
Section: Dow Europe Gmbhmentioning
confidence: 99%